Vaccine hesitancy and equity: lessons learned from the past and how they affect the COVID-19 countermeasure in Indonesia - Rano K. Sinuraya; Rina F. Nuwarda; Maarten J. Postma; Auliya A. Suwantika (BMC, 2024)
Abstract Introduction Indonesia has made progress in increasing vaccine coverage, but equitable access remains challenging, especially in remote areas. Despite including vaccines in the National Immunization Program (NIP), coverage has not met WHO and UNICEF targets, with childhood immunization decreasing during the COVID-19 pandemic. COVID-19 vaccination has also experienced hesitancy, slowing efforts to end the pandemic. Scope This article addresses the issue of vaccine hesitancy and its impact on vaccination initiatives amidst the COVID-19 pandemic. This article utilizes the vaccine hesitancy framework to analyze previous outbreaks of vaccine-preventable diseases and their underlying causes, ultimately providing recommendations for addressing the current situation. The analysis considers the differences between the pre-pandemic circumstances and the present and considers the implementation of basic and advanced strategies. Key findings and conclusion Vaccine hesitancy is a significant challenge in the COVID-19 pandemic, and public health campaigns and community engagement efforts are needed to promote vaccine acceptance and uptake. Efforts to address vaccine hesitancy promote trust in healthcare systems and increase the likelihood of individuals seeking preventive health services. Vaccine hesitancy requires a comprehensive, culturally sensitive approach that considers local contexts and realities. Strategies should be tailored to specific cultural and societal contexts and monitored and evaluated.